The Existence and Significance of Local Islam Amid Purification and Modernization in Indonesia - Kusnan, Kusnan; Basit, Abdul (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Religion and social values in an area cannot be separated, eventually becoming part of people's lives. This system is able to give birth to traditions that meet the wishes of the community. Providing socio-religious benefits, such as the traditions of nyadran, ba'da kupat and ngapati that developed for a long time and existed in the community. Javanese Islam is a form of cultural acculturation, which brings together Islam as a great tradition with Javanese culture as a little tradition. The Javanese Islam shown is actually the local genius of the Javanese people in responding to Islam as a great tradition, which gives birth to a unique religious character. Islamic teachings became part of the ritual, which was thick with Javanese culture fused with each other. This phenomenon makes Javanese Islam able to be side by side with elements of modernization. While the purification of Islam continues, the tradition in its development into a religious ethic that gives birth to community harmony, realizing religious social stability. Writings based on literature methods, interviews and in-depth observations, raise the existence and relevance of Javanese (local) Islam in the midst of rapid modernization and purification in Indonesia.